Halal hospitality for senior citizens in Malaysia: an analytical study from an Islamic perspective - Fadhli, Ahmad Syarief; Fatah Yasin, Raudlotul Firdaus; Kamal Koh, Syamilah Heng (HH Publisher, 2020)
Malaysia, as reported by the Department of Statistics Malaysia, will be an ageing nation by 2035. Yet, the rapidly increasing population of the elderly in tandem with the decreasing fertility and morbidity rate cause imbalance in the society’s structure. The elderly are often perceived negatively because of the stereotype, and it affects their physical and mental health. Employing qualitative methodology, this study tries to define the meaning of the elderly from the Islamic perspective and attempts to provide the halal key concepts as guidelines to improve hospitality. This will be undertaken after analysing the caretaking system in Malaysia using deductive and inductive methods. This research hypothesised that the current caretaking system is progressing, but more drastic initiatives areneeded to achieve a wholesome objective for the elderly’s well-being from the Islamic perspective.